Do firms facing competitors from emerging markets behave differently? Evidence from Austrian manufacturing firms - Klaus S. Friesenbichler; Andreas Reinstaller (Austrian Institute of Economic Research (WIFO), 2021)
We study the strategic positioning of Austrian manufacturing firms that face competition from emerging markets as opposed to firms that do not. Using a unique sample of large Austrian manufacturing, we find that emerging market competitors are not always a force majeure, but the result of the firms' international activity. Existing strengths and weaknesses are more pronounced when firms face competitors from emerging markets. Emerging market competition is associated with a broader product portfolio and triggers portfolio adjustments. Yet, a larger share of the companies facing emerging market competitors neither adjusts the product portfolio nor plans to develop new competences.
Keywords: L20; L60; M16; 330; Emerging Markets; Competition; Manufacturing; Austria; Dynamic Capabilities